CONCEPTUALIZATION OF THE INTERNATIONAL COOPERATION IN THE FIELD OF SCIENCE AND TECHNOLOGY - E. S. Zinovieva (MGIMO University Press, 2019)
The development of science and technology, in particular information and communication technologies, has a significant impact on world political processes. It strengthens globalization and interdependence, expands the number of actors in world politics by strengthening the capabilities of non-state actors, it transforms national sovereignty, and also leads to the emergence of new, high-tech challenges and threats to international and national security. Due to their transnational nature overcoming these challenges and threats implies cooperation between different types of actors in world politics. Multiplicity of actors, as well as the complexity, variability and pervasive nature of the subject of cooperation (technology), make traditional rationalist schools of thought not quite suitable for studying this sphere of world politics. On the basis of a critical review of the prevailing approaches to the study of science and technology in international relations, the author argues that the most promising theoretical school of thought in this field is social constructivism. It shows that technology is embedded in social relations, there is a constitutive relationship between technology and social structures. Therefore, the characteristics and implementation of technology can become the subject of political competition, including the international level. The spread of technology leads to the globalization of social structures and relations that are tied to them, which initially had a local origin. Naturally, this process is accompanied by political rivalry, generating resistance from agents of alternative social structures.As a case study to evaluate the analytical potential of this approach, the article deals with the issues of Internet governance and international information security. It is shown that since the creation of the Internet, its characteristics and governance were largely determined by the national interests of the United States, resulting in a public-private governance model in the form of ICANN. Due to the proliferation of the Internet, its technological features and characteristics of the established governance model influence policies and practices of international relations in the field of information and communication technologies. Multi-level cooperation formats have spread within the UN, bringing together representatives of states, business, civil society and the research community. First of all, it is the Internet Governance Forum created in 2006. However, such models of international cooperation do not fully correspond to the remaining statist characteristics of the modern international system, as a result they undergo adjustment. Thus, in the field of information security, non-state actors have only consulting powers, while the key format of interaction remains intergovernmental cooperation. It seems that the global regime of Internet governance is developing in this direction.